DIDACTIC POSSIBILITIES OF USING MOTIVATIONAL TECHNOLOGIES IN PHYSICAL EDUCATION LESSONS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article is about the didactic possibilities of using motivational technologies in physical education lessons. Concepts of motivation and the main theories of its formation are considered, they describe various psychological characteristics of motivations for sports, which can be determined by evaluating success levels and educational activities. Psychological characteristics of students' motivation to play sports are studied.